Hybrid-Immersive Learning Media: Validity, Practicality, and Effectiveness of an Audio-Comic Video Integrated with Marker-Based Augmented Reality - Surya Satar; Nurbaya Nurbaya; Hanida Listiani; Cartika Candra Ledoh; Rosaniya E. Rehiara (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
The Human Excretory System is an abstract, microscopic topic that often causes student misconceptions. This R&D study, using the ADDIE model, developed an Audio-Comic Video integrated with Marker-Based Augmented Reality (AR), using Assemblr 3D assets to interactively visualize excretory organs. The subjects were eleventh-grade students at SMAS Muhammadiyah Jayapura. Validation results showed the medium was very valid according to the material expert (92.22%) and valid according to the media expert (81.25%). Practicality tests with students (93.57%) and teachers (88.57%) fell into the very practical category. The effectiveness test on 35 students showed scores increasing from 50.02 (pretest) to 84.07 (posttest), with an N-Gain of 0.626 (medium category) and a significant difference (Sig. 2-tailed = 0.000). The medium proved feasible and effective as an alternative biology learning medium accommodating visual, auditory, and kinesthetic learning styles.